2006
DOI: 10.1111/j.1365-2761.2006.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mycobacteria in clinically healthy ornamental fish and their aquarium environment

Abstract: Some mycobacterial species (particularly Mycobacterium marinum) found in aquarium environments may cause chronic diseases in fish and cutaneous infections in humans, the so-called 'fish tank granuloma'. The presence and distribution of mycobacterial species in clinically healthy aquarium fish and their environment has not been adequately explored. The present study analysed the occurrence of mycobacteria in a decorative aquarium (Brno, South Moravia) and in five aquaria of a professional fish breeder (Bohumin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 42 publications
1
94
1
3
Order By: Relevance
“…Mycobacteria are common pathogens of zebrafish (Astrofsky et al 2000; Kent et al 2004) and have been found at background levels in previous studies without clinical signs of disease (Beran et al 2006; Harriff et al 2007; Zanoni et al 2008; Whipps et al 2008). We have shown that stress exacerbates mycobacterial infections in zebrafish (Ramsay et al in press).…”
Section: Discussionmentioning
confidence: 98%
“…Mycobacteria are common pathogens of zebrafish (Astrofsky et al 2000; Kent et al 2004) and have been found at background levels in previous studies without clinical signs of disease (Beran et al 2006; Harriff et al 2007; Zanoni et al 2008; Whipps et al 2008). We have shown that stress exacerbates mycobacterial infections in zebrafish (Ramsay et al in press).…”
Section: Discussionmentioning
confidence: 98%
“…are commonly found in sea water and likely represent opportunistic invaders or potential members of normal skin flora. 7,43 Although a variety of Gram-negative bacteria were isolated from skin lesions, no species of bacteria was consistently isolated. Cutaneous lesions in the seadragons were often advanced when examined histologically so that a determination as to whether the inciting lesion was bacterial, fungal, or traumatic was not possible.…”
mentioning
confidence: 99%
“…It is possible that these two fish had pre-existing background infections, as we have documented minimal background mycobacteriosis in zebrafish at the laboratory providing the fish for the present study (Kent et al 2004, Kent et al 2011). Mycobacterium species capable of causing disease in fish may occur in aquaria in the absence of disease (Beran et al 2006). Indeed, all groups of the fish in this study, including controls that were not deliberately exposed to mycobacteria, exhibited the presence (perhaps colonization) of large amounts of acid-fast bacteria in the intestinal lumen.…”
Section: Discussionmentioning
confidence: 99%